COMPUTED TOMOGRAPHY CHARACTERISTICS OF ACUTE TRAUMATIC EPIDURAL HEMATOMA IN SURGICALLY TREATED PATIENTS AT MILITARY HOSPITAL 103 - Tran Anh Duc; Nguyen Thanh Bac (Tạp chí Y học Quân sự, 2026)
Objectives: To describe the computed tomography characteristics of acute traumatic epidural hematoma in surgically treated patients. Subjects and methods: A cross-sectional descriptive study was conducted in 68 patients diagnosed with traumatic epidural hematoma who underwent surgery at the Department of Neurosurgery, Military Hospital 103, from January 2024 to June 2025. Computed tomography characteristics were evaluated, including hematoma location, density, volume, degree of midline shift, and skull injury. Results: Most patients had a unilateral hematoma (97.1%), predominantly located in the temporal region (39.7%), with hyperdense appearance on CT (85.3%). Hematoma volume was mainly 30-60 mL (47.1%), and midline shift < 5 mm was observed in 36.8% of patients. Skull injury was present in 92.6% of cases. Conclusions: On computed tomography, acute traumatic epidural hematoma commonly appears as a hyperdense lesion, usually located in the temporal region, and may be associated with midline shift.